Non-Governmental Organizations' Involvement in Poverty Alleviation in Bangladesh - Taylor N Scheffing (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
Labeled as one of the poorest countries in the world, Bangladesh is accustomed to poverty. Beginning in the late 1970s and even more since the arrival of the millennium, Bangladesh had made significant strides towards economic development through poverty alleviation efforts brought on by the World Bank initiatives. However, widespread discontent with the World Bank has led to increased, dominant presence and involvement from non-governmental organizations. Non-governmental organizations typically share a public mission, where those in Bangladesh aim to work exclusively with those in disadvantaged, rural areas. This paper will be addressing the growing question: what are non-governmental organizations (NGOs) doing to alleviate Bangladesh’s level of poverty?
Keywords: bangladesh; poverty; poverty alleviation; poverty eradication; NGO; non-governmental organizations